2018
DOI: 10.1007/s00181-018-1616-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of productive and non-productive government expenditure on economic growth: an empirical analysis in high-income versus low- to middle-income economies

Abstract: This paper examines the relationship between the compositions of government expenditure and economic growth. It develops an endogenous growth framework drawing on variables from existing models, and separates government expenditure into productive and non-productive forms. Using panel data from 37 high-income and 22 lowto middle-income countries covering 1993-2012, our findings are based on OLS fixed effects and GMM techniques. We challenge much of the existing empirical literature in relation to developing ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 39 publications
5
41
0
Order By: Relevance
“…Government expenditure is a part of government spending as a form of fiscal policy set out in the APBN (Anitasari & Soleh, 2015) .Government spending is allocated productively could have an impact on the economy of a country (Chu, Hölscher, & McCarthy, 2020).Government expenditure that is right on target will affect the progress and welfare of the community, price stability, increase productivity and the growth of job opportunities, so that government spending can have an impact on the rate of economic development.…”
Section: Government Expenditurementioning
confidence: 99%
“…Government expenditure is a part of government spending as a form of fiscal policy set out in the APBN (Anitasari & Soleh, 2015) .Government spending is allocated productively could have an impact on the economy of a country (Chu, Hölscher, & McCarthy, 2020).Government expenditure that is right on target will affect the progress and welfare of the community, price stability, increase productivity and the growth of job opportunities, so that government spending can have an impact on the rate of economic development.…”
Section: Government Expenditurementioning
confidence: 99%
“…These outcomes contradict the 'a prior expectations' of this study. Studies stressed that human capital development increases output (Chu, Holscher & McCarthy, 2020;Popoola, Alege, Gershon & Asaleye, 2019;Blanchard, 2010, Katema, 2000Glumm & Ravikummar, 1997). NPE, ACAP1 and PVIT are economically significant.…”
Section: Presentation Of the Resultsmentioning
confidence: 99%
“…Consequently, the study by Devarajan, Swaroop and Zou (1996) classified government expenditure into two, namely productive expenditure and non-productive expenditure. A recent study by Chu, Holscher and McCarthy (2020) investigate how productive and non-productive government expenditure affect economic growth in high-income and middle -income economies. The scholars reported that diverting government expenditure from non-productive to productive channels would improve growth both in the short and long-run.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has devoted a great deal of attention to the issue of the relationships between the amount of public expenditure and economic growth at a country level (Modigliani and Sterling 1986;Barro 1990;Butkiewicz and Yanikkaya 2011;Wu et al 2010). Researchers have differentiated between productive and non-productive government expenditure, and have shown how a country can increase its economic growth by changing the mix between these alternative forms of expenditure (Gemmell et al 2015;Chu et al 2018).…”
mentioning
confidence: 99%